Gut Microbiota: A New Challenge in Mood Disorder Research - Giuseppe Marano; Sara Rossi; Greta Sfratta; Gianandrea Traversi; Francesco Maria Lisci; Maria Benedetta Anesini; Roberto Pola; Antonio Gasbarrini; Eleonora Gaetani; Marianna Mazza (Life)
The gut microbiome has emerged as a novel and intriguing focus in mood disorder research. Emerging evidence demonstrates the significant role of the gut microbiome in influencing mental health, suggesting a bidirectional communication between the gut and the brain. This review examines the latest findings on the gut–microbiota–brain axis and elucidates how alterations in gut microbiota composition can influence this axis, leading to changes in brain function and behavior. Although dietary interventions, prebiotics, probiotics, and fecal microbiota transplantation have yielded encouraging results, significant advances are needed to establish next-generation approaches that precisely target the neurobiological mechanisms of mood disorders. Future research must focus on developing personalized treatments, facilitated by innovative therapies and technological progress, which account for individual variables such as age, sex, drug history, and lifestyle. Highlighting the potential therapeutic implications of targeting the gut microbiota, this review emphasizes the importance of integrating microbiota research into psychiatric studies to develop more effective and personalized treatment strategies for mood disorders.